An exploration of participants’ views and experiences of cultural museums and their challenges - Dabamona, Jufri; Dabamona, Samsudin Arifin (Gelar: Jurnal Seni Budaya, 2023)
Cultural museums have always been considered guardians of culture, promoting the core concepts of cultural preservation and conservation. This paper delves into the challenges faced by two cultural museums from various perspectives and examines the transformation of museums in supporting Papuan culture through values centered on conservation and preservation, as gleaned from the experiences and views of the participants. This study is qualitative research that employs an interpretive strategy, with participants including museum personnel, cultural agencies in Papua Province, academics, and teachers from Cenderawasih University. Data were collected through in-depth interviews, field observations, and literature studies. The study identified three themes: (1) Collection and space management, (2) Museum image, and (3) Capacity building and moral responsibility of human resources. To enhance cultural services, the study suggests that museums in Papua need to focus on strengthening collection management, enhancing visitor convenience, and providing increased staff support in the cultural field.